An Analysis of Students’ Mathematical Understanding in Solving Pythagorean Theorem Problems in Eighth Grade - Fadillah, Rizki; Rifki, Muhammad (Papanda Publisher, 2024)
Mathematical comprehension ability can be achieved well if students really understand the concept. This study aims to determine the mathematical comprehension ability of junior high school students in North Pontianak District on the Pythagorean theorem material. The method used in this research is qualitative with descriptive data analysis. This research used 3 students of class VIII of SMP Negeri 15 as subjects, namely 2 females and 1 male. The data collection technique in this study was carried out using a test in the form of essay questions and accompanied by questions and answers to the research subjects. Based on the results and discussion of the study, the mathematical comprehension ability of students in understanding problems, planning solutions, and re-checking all the steps that have been done is classified as moderate, with a percentage of 75%. The mathematical comprehension ability and the quality of improving the mathematical comprehension ability of students whose learning is applied are better and students have a more positive attitude towards the learning, making this learning an alternative learning that teachers can apply